Investigating critical metals Ge and Ga in complex sulphide mineral assemblages using LIBS mapping - Coron, J.; Papier, S.; Decrée, S.; Ferreira, V.; Duponchel, L.; Baele, J.M. (Spectrochimica acta. Part B: Atomic spectroscopy, 2024)
Elemental imaging using Laser-Induced Breakdown Spectroscopy (LIBS) mapping is increasingly applied to a wide range of materials. In geomaterials, phase identification and characterization (mineralogy) are crucial for solving a variety of problems in earth sciences and mining industry. Here we applied LIBS mapping to ore samples from the world-class Kipushi deposit, Democratic Republic of Congo, because these ores are known for their great mineral complexity and economic value, especially for their high potential in critical metals such as Ge and Ga. The mineralogy of the samples was reconstructed by combining two approaches: 1) element colocalization in LIBS maps that were selected based on the knowledge of occurring mineral species at the site and 2) correlation maps obtained by applying the Interesting Features Finder (IFF) algorithm. Reconstructed minerals include chalcopyrite, bornite, chalcocite, sphalerite, galena, pyrite, tennantite-(Zn), renierite, tungstenite, betekhtinite, carrollite, gallite, and a series of non-sulphide gangue minerals (quartz, carbonate and clay minerals). SEM-EDS was used to confirm the LIBS-derived mineralogy, especially for sub-pixel inclusions. Among other results, Ge and Ga are hosted as major elements in renierite and gallite, respectively, and also as trace-elements in chalcopyrite, bornite and tungstenite (for Ge), and chalcopyrite, bornite, sphalerite and renierite (for Ga). Particular attention was paid to iron interfering with gallium at 417.20 nm, for which simple background-corrected peak intensities were compared to a more advanced chemometric method (MCR-ALS). All the results were obtained with minimal time and efforts and, while only qualitative in nature, they already provide essential information about ore texture, mineralogical composition and trace-element distribution across the ore. [Display omitted] •LIBS mapping was applied to complex geomaterials (ores) that include Ge and Ga, from Kipushi, Democratic Republic of Congo.•Mineral maps were produced by combining elemental LIBS maps with Interesting Features Finder (IFF) algorithm.•The distribution of trace-element germanium and gallium were investigated within the framework of the mineral maps.